HUBUNGAN PENERIMAAN DIRI DAN TINGKAT STRES PADA PENDERITA DIABETES MELLITUS - Yan, Loriza Sativa; Marisdayana, Rara; Irma, Rizki (Jurnal Endurance, 2017)
Diabetic Mellitus caused many complications if itâs not treated properly. This condition has been changed several of physical or psychological disturbances for diabetic patientâs health status such as stress. Previous research showed that diabetic patients often become discouraged in controlling the diabetic complications. This study aimed to identify the relationship between self acceptancereâs and stress level among diabetic patients in Kota Jambi. The method of this study is quantitative with crossectional design, by using accidental sampling to collect of 77 samples. Instrument used the Bergerâs self-acceptance questionnaire; data were analyzed by Spearmanâs rank test. The research results showed majority respondents were Diabetes Mellitus patients those women who aged 45-60 years old. The respondents had moderate stress level and poor self-acceptance. This finding indicated that a relationship between self acceptances with level of stress among Diabetes Mellitus patients. Further investigation, improving stress program of diabetic complications in order to repair psychological health status is recomended.